Choice of costimulatory domains and of cytokines determines CAR T-cell activity in neuroblastoma. (3rd June 2018) - Quintarelli, Concetta; Orlando, Domenico; Boffa, Iolanda; Guercio, Marika; Polito, Vinicia Assunta; Petretto, Andrea; Lavarello, Chiara; Sinibaldi, Matilde; Weber, Gerrit; Del Bufalo, Francesca; Giorda, Ezio; Scarsella, Marco; et al.
ABSTRACT: Chimeric antigen receptor (CAR) T-cell therapy has been shown to be dramatically effective in the treatment of B-cell malignancies. However, there are still substantial obstacles to overcome, before similar responses can be achieved in patients with solid tumors. We evaluated both in vitro and in a preclinical murine model the efficacy of different 2nd and 3rd generation CAR constructs targeting GD2, a disial-ganglioside expressed on the surface of neuroblastoma (NB) tumor cells. In order to address potential safety concerns regarding clinical application, an inducible safety switch, namely inducible Caspase-9 (iC9), was also included in the vector constructs. Our data indicate that a 3rd generation CAR incorporating CD28.4-1BB costimulatory domains is associated with improved anti-tumor efficacy as compared with a CAR incorporating the combination of CD28.OX40 domains. We demonstrate that the choice of 4-1BB signaling results into significant amelioration of several CAR T-cell characteristics, including: 1) T-cell exhaustion, 2) basal T-cell activation, 3) in vivo tumor control and 4) T-cell persistence. The fine-tuning of T-cell culture conditions obtained using IL7 and IL15 was found to be synergic with the CAR.GD2 design in increasing the anti-tumor activity of CAR T cells. We also demonstrate that activation of the suicide gene iC9, included in our construct without significantly impairing neither CAR expression nor anti-tumor activity, leads to a prompt induction of apoptosis of GD2.CAR T cells. Altogether, these findings are instrumental in optimizing the function of CAR T-cell products to be employed in the treatment of children with NB.